A persistent (amino)(ferrocenyl)carbene() - DeHope, Alan (2011)
Deprotonation of N,N-diisopropyl-C-ferrocenylaldiminium triflate 2 cleanly leads to the corresponding 1,2-diamino-1,2-diferrocenylethene 3, the dimer of the desired (amino)(ferrocenyl)carbene. Fulvene 6, obtained by addition of the lithium salt of tetramethylcyclopentadiene to methoxyformamidinium methylsulfate 5, reacts with dicarbonylcyclopentadienylbromoiron(II), and with a mixture of FeCl(2) and Cp* lithium salt, affording the corresponding tetramethylferrocenylaldiminium salt 7, and nonamethylferrocenylaldiminium salt 8, respectively. Although the deprotonation of 7 gives a complex mixture of products, the treatment of 8 at −78 °C with sodium hexamethyldisilazide allowed for the isolation of the corresponding (amino)(ferrocenyl)carbene 9 as a yellow powder. However, even in the solid state, it is stable for less than 48 h at −20 °C. In addition to NMR spectroscopy, evidence for the carbene nature of 9 was found by a trapping experiment with sulfur that leads to the corresponding adduct 10, which was characterized by a single crystal X-ray diffraction study.